Kartini and the Women's Movement: An Analysis of Her Role and Influence in the History of the Indonesian National Movement - Burhanuddin (CV. Creative Tugu Pena, 2024)
Discussions pertaining to the role of women are an ongoing phenomenon. The debates surrounding women's roles as actors of domestic work or their role in the public sphere are not obsolete discourses that are ubiquitous in academic discourse. One such debate concerns the women's movement. The objective of the movement, which was initiated by women activists, is to enhance the status of women. The actions of prominent female figures throughout history demonstrate that Indonesian women were instrumental in establishing the women's movement, guided by principles of humanity and social justice. This study seeks to establish a historical understanding as a foundation for the contemporary women’s movement in its pursuit of social and political rights. In order to gain insight into the fluctuating nature of the women's movement since the late nineteenth century, the historical method was employed in this research. It became evident that the waves of activism initiated by female leaders, advocating for women's rights in all fields, were born out of the injustices inherent in gender relations. Indonesian women leaders, in particular, have set an exemplary standard, and it falls upon today's women to carry the torch and continue the struggle